2007
DOI: 10.1002/app.27546
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(ethylene glycol) crosslinked chitosan films

Abstract: Poly(ethylene glycol) (PEG) crosslinked chitosan films with various PEG to chitosan ratio and PEG molecular weight were successfully prepared via the epoxy-amine reaction between chitosan and PEG-epoxy. The thermal and mechanical properties and swelling behavior were studied for the PEG crosslinked chitosan films. The mechanical strength of chitosan films were greatly enforced by the introduction of PEG-epoxy, achieving an elongation of about 80%. It was found that the crosslinked chitosan films form hydrogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 39 publications
0
48
1
Order By: Relevance
“…Alkhamis et al [22] have reported the methanol vapor absorption characteristics of chitosan using the BET isotherm theory and found a high value of heat of interaction parameter (C-value of 10), indicating the presence of strong polar interactions between methanol and chitosan molecules. The EGDE molecules contain epoxy functionalities which interact with free amino groups of chitosan and form cross-linked networks among the polymer chains [10,23]. No heterogeneities or phase segregations in the films were observed during processing and treatment with methanol and EGDE.…”
Section: Processing Characteristics Of Chitosan Filmsmentioning
confidence: 91%
See 1 more Smart Citation
“…Alkhamis et al [22] have reported the methanol vapor absorption characteristics of chitosan using the BET isotherm theory and found a high value of heat of interaction parameter (C-value of 10), indicating the presence of strong polar interactions between methanol and chitosan molecules. The EGDE molecules contain epoxy functionalities which interact with free amino groups of chitosan and form cross-linked networks among the polymer chains [10,23]. No heterogeneities or phase segregations in the films were observed during processing and treatment with methanol and EGDE.…”
Section: Processing Characteristics Of Chitosan Filmsmentioning
confidence: 91%
“…In the case of methanol and methanol plus EGDE treated films (CTS-2 and CTS-3), the endothermic peak position was shifted to higher temperature compared to untreated chitosan film (CTS-1), possibly due to strong interactions of methanol and/or water with chitosan molecules. While EGDE is used, the cross-linking occurs between the epoxy group of EGDE and the amino group of chitosan [10,23]. Therefore, the cross-linked chitosan (CTS-3) has less free amino groups available to form hydrogen bonds with water molecules.…”
Section: Thermal Transition Characteristicsmentioning
confidence: 99%
“…Lysozyme from hen egg white (50,000 U/mg) was purchased from Merck Co., Japan and was used without further purification. The diepoxyPEGs were synthesized according to the method reported by Laine et al 21 The PEG-crosslinked chitosan hydrogel films were synthesized according to the method reported by Kiuchi et al 15 The sample codes, molecular weight of PEG and reactant compositions are shown in Table I. The chitosan/diepoxyPEG blend films for DSC measurement were prepared by casting method from 0.4% acetic acid solution, and their sample codes and blend ratio are also shown in Table I.…”
Section: Experimental Section Materialsmentioning
confidence: 99%
“…It was found that an introduction of the cross-linked structure in chitosan network improves mechanical properties of chitosan hydrogel films. 15 In this article, the cross-linked structure and the behavior of enzymatic degradation at physiological conditions using hen egg white (HEW) lysozyme will be investigated for the PEG-cross-linked chitosan hydrogel films. As the b-(1-4)-linked GlcNAc sequence of chitosan is degraded by HEW lysozyme as well as human lysozyme, 16,17 the PEG-crosslinked chitosan hydrogel is expected to be degraded by lysozyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation